Emotional intelligence, job satisfaction and alcohol consumption in nursing staff - Julia Lizeth, Julia Lizeth; Armendáriz-García, Nora Angélica; Sánchez-Gómez , Martín; Alonso Castillo, María Magdalena; López García, Karla Selene (Horizonte Sanitario, 2023)
Objective: To know the relationship between emotional intelligence, job satisfaction and alcohol consumption in nursing staff working in a tertiary care hospital. Materials and methods: Descriptive, cross-sectional, and correlational study. The sample consisted of 129 nursing professionals who work in a third level hospital, divided into critical and non-critical areas. The instruments used were a Socio-demographic Data Sheet, Trait Meta Mood Scale (TMMS-24), Job Satisfaction Questionnaire S10/12 and AUDIT. Results: 75% were women, with undergraduate studies, more than 45% consumed in the last week. It was found that there is a positive and significant relationship between emotional intelligence and job satisfaction (rs = .236, p < .001), a negative and significant relationship was also found between job satisfaction and alcohol consumption (rs = -.195, p < .05). Conclusions: Differences are shown between EI, job satisfaction and alcohol consumption in nursing staff according to the area in which they work. Likewise, there is a positive relationship between EI and job satisfaction and a negative relationship between job satisfaction and alcohol consumption. This study demonstrates the importance of knowing in depth what factors impact the care provided by nursing staff within hospital services and what are the methods used to deal with them. Key Words: Emotional intelligence; alcohol; public health; nursing.